1993
DOI: 10.1002/hep.1840170417
|View full text |Cite
|
Sign up to set email alerts
|

Decreased mitochondrial oxidation of fatty acids in pregnant mice: Possible relevance to development of acute fatty liver of pregnancy

Abstract: Severe impairment of the beta-oxidation of fatty acids, as a consequence of a single factor or a combination of different causes, leads to microvesicular steatosis of the liver. In an effort to understand the mechanism(s) leading to the development of acute fatty liver of pregnancy in some women, we determined the effects of pregnancy on the mitochondrial oxidation of fatty acids in mice. In vivo, the rate of oxidation of the whole fatty-acid chain length was determined by measuring the rate of exhalation of [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
3

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(31 citation statements)
references
References 45 publications
1
27
0
3
Order By: Relevance
“…5 It has also been suggested that pregnancy may be associated with low levels of riboflavin and this may potentiate the development of mitochondrial toxicity caused by nucleoside analogues. 6 Riboflavin is a precursor for the flavoprotein co-factors required for oxidative phosphorylation and the production of ATP.…”
Section: Discussionmentioning
confidence: 99%
“…5 It has also been suggested that pregnancy may be associated with low levels of riboflavin and this may potentiate the development of mitochondrial toxicity caused by nucleoside analogues. 6 Riboflavin is a precursor for the flavoprotein co-factors required for oxidative phosphorylation and the production of ATP.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, triglyceride synthesis is decreased in adipose tissue, whereas lipolysis is enhanced during pregnancy (18), resulting in an increase in serum free fatty acid levels. In the liver, pregnancy leads to a reduction in fatty acid oxidation (15), although fatty acid synthesis is increased (62). The increase in de novo fatty acid synthesis and the enhanced delivery of fatty acids from adipose tissue coupled with the decrease in fatty acid oxidation increase the pool of fatty acids available in the liver, resulting in an increase in triglyceride synthesis (58).…”
Section: In Many Animals Including Humansmentioning
confidence: 99%
“…They may reflect adaptive changes because they also occurred after estrogen/progesterone treatment or pregnancy in rats, associated with decreased mitochondrial oxidation. 138,139 Thus, pathological liver apoptosis in patients treated with TGZ does not seem to be a key mechanism for TGZ-induced liver injury.…”
Section: Liver Apoptosis and Mitochondrial Abnormalities In Patientsmentioning
confidence: 99%